TI_GERICHTE 14.2003.88 vom 2. Februar 2006 , Appello contro rigetto provvisoiro dell'opposizione. Stralcio. - TI Tribunale d'appello (2006)
Appello contro rigetto provvisoiro dell'opposizione. Stralcio.